Influence of Styrene-Acrylic Ester Dispersion on the Early Hydration of Cement - Ru Wang; Xiaoxin Shi (Advances in Materials Science and Engineering)
Early hydration of cement in the presence of styrene-acrylic ester (SAE) dispersion was investigated, and the hydration heat, hydration degree, and hydrates were analyzed using isothermal calorimeter, XRD, and ESEM. The results show that SAE dispersion prolongs the induction period, postpones and shortens the accelerating period, and inhibits the decelerating and stable periods of cement hydration. The hydration heat and hydration degree of cement in the presence of SAE dispersion are less than those of the control. SAE dispersion inhibits the formation of C4AH13 and thus AFt, and more SAE dispersion brings stronger influence, but it enhances the stability of AFt. AFt generation during the early hydration period is controlled gradually by the reaction of C4AH13 generation with increasing SAE dispersion, but this is controlled by the reaction of C4AH13 consumption for the control paste. Besides, SAE dispersion retards and inhibits the formation of CH and C-S-H and also changes their morphology.